Miroslav Šašek with 119 illustrations - Salisbury, Martin (Thames and Hudson, 2021)
Czech artist Miroslav Sasek (1916-1980) was remarkable for his unique and pioneering approach to non-fiction picture books, illustrating daily life as if seen from a child's perspective. His bestselling This Is... series eventually totalled eighteen books. A witty collection of travel guides for children, the books employ an avant-garde synthesis of word and image that captures the joyous idiosyncrasies of life and culture in cities and countries around the world. With great insight, acclaimed author Martin Salisbury analyses Sasek's multifarious oeuvre, and how he became one of the twentieth century's most beloved and significant contributors to the world of picture books. The artist's charming travelogues continue to appeal to adults and children alike, even in a digital age exploding with travel imagery. In this beautifully designed book, illustrated with sketches and original artwork, and featuring examples spanning from Greece to Hong Kong, Rome to San Francisco, Ireland to Israel and more, Sasek's best-known works come alive alongside lesser-known aspects of his practice, such as painting and puppet-making.
Keywords: Sasek, Miroslav -- 1916-1980; Sasek, M. / (Miroslav) / 1916-1980 / Criticism and interpretation; Illustrators / Czech Republic / Biography; Illustrators; Czech Republic; Biographies; Criticism, interpretation, etc